Instrument to Assess the Farmers’ Participation in Effective Canal Irrigation Management - Naik, Akkamahadevi; Shivamurthy, M.; Gowda, M.J. Chandre (Indian Journal of Extension Education, 2019)
In the present study, an attempt was made to develop an instrument to measure the farmers’ participation in effective canal irrigation management. The method of summated rating scale suggested by Likert (1932) and Edwards (1969) were followed to develop an instrument through six stages viz., identification of dimension, collection of items/statements, relevancy analysis, item analysis, reliability and validity of the scale. Based on the review of literature and discussion with experts in the related areas, six dimensions viz., farmers’ participation in formulation of guidelines, planning and implementation activities, maintenance activities, responsibility sharing, crop planning activities and integrated crop management were listed and 60 items/statements were enlisted. Based on the relevancy percentage equal and more than 80.00 per cent and mean relevancy score of equal and more than 4.00 were considered for inclusion in the item analysis. After the relevancy analysis and item analysis, out of 60 items/statements, 34 statements were retained. In order to compute the scale values for each of the identified dimensions by adopting normalized ranking method recommended by Guilford (1954) and the total scale value ranges from 9.340 to 2.537, with farmers’ participation in integrated crop management got highest rank and formulation of guidelines got lowest rank. The developed instrument was found to be reliable (0.96) and valid (0.98), hence it can be used to measure the farmers’ participation in effective canal irrigation management.
Keywords: Canal irrigation management; Famers’ participation; Relevancy; Reliability; Validity